Assessing mathematics within advanced school science qualifications - McAlinden, Mary; Noyes, Andrew (Taylor & Francis, 2017)
Following sustained discussion regarding the relationship between advanced mathematics and science learning in England, the Government has pursued a reform agenda in which mathematics is embedded in national, high stakes A-level science qualifications and their assessments for 18-year-olds. For example, A-level Chemistry must incorporate the assessment of relevant mathematics for at least 20% of the qualification. Other sciences have different mandated percentages. This embedding policy is running in parallel with an adding policy that is encouraging all young people to include the study of mathematics to 18. In this paper we present a detailed scrutiny of the published sample assessment materials in the new A-level Physics, Chemistry and Biology qualifications in order to consider what the impact of this policy move might be for the teaching and learning of mathematics, its applications in upper secondary school advanced science studies and the implications in the transition to mathematically-demanding undergraduate studies.